The Role of Corporate Social Responsibility Decoupling on Corporate Tax Avoidance - Imam Nazarudin Latif; Liona Efrina; Nur Ika Mauliyah (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
Tax avoidance is an issue that continues to generate debate and controversy for its ethics in the business world. Corporate Social Responsibility (CSR) has emerged as a significant factor in bridging the gap between government needs for tax revenues and corporate goals for economic growth. However, based on neo-institutional theory, companies may only show CSR symbolically without taking appropriate concrete actions, creating a gap between communication and actions related to CSR. This action, called CSR decoupling, can create the risk of greenwashing, namely the practice of deceiving the public about a company's environmental or social performance. Therefore, this study aims to investigate the relationship between CSR decoupling and tax avoidance. This exploratory and quantitative research used companies in the food and beverage industry for 2019-2021. Using the purposive sampling method, out of 23 from 72 companies selected, and 69 data were processed with SPSS. The results show that CSR decoupling positively influences tax avoidance, even after the robustness test. This result implies that companies that carry out CSR decoupling tend not to comply with tax regulations formally, although not substantially. The result also depends on the size of the audit committee, the size of the company, and the return on assets. These findings might be useful for policymakers, shareholders, management and board members, audit committees, and investors.